DO SALES VOLUME AND COST OF GOOD SOLD INCREASE GROSS PROFIT MARGIN - Fauzi, Abdul Aziiz Ahmad; Rifada, Regina Maurizka; Cahyani, Debi (Jurnal Ilmu Akuntansi dan Bisnis Syariah (AKSY), 2024)
This study, conducted in the context of Islamic Economics, examines PT's Gross Profit Margin (GPM). Unilever Indonesia Tbk. from 2013 to 2022, focusing on the effects of sales volume and Cost of Goods Sold (COGS). The research aims to identify how these factors influence GPM, a key metric in Islamic Economics. A quantitative descriptive method was used to analyze secondary data from financial statements. The population in this study includes all nominal sales data, cost of goods sold, and gross profit margin ratios of PT. Unilever Indonesia Tbk. Unilever Indonesia Tbk. Unilever Indonesia Tbk. Unilever Indonesia Tbk. Classical assumption tests, determination coefficient tests, F-tests, and t-tests were conducted. Results indicate that sales volume positively impacts GPM, while COGS negatively affects it. Effective sales volume and COGS management are crucial for optimizing gross profit margins, suggesting businesses should focus on these areas to enhance profitability. These findings have practical implications, as they imply that businesses should prioritize strategies that increase sales volume and efficiently manage COGS to enhance profitability. By understanding the critical relationship between these variables and GPM, companies can make informed decisions that contribute to their financial health and competitiveness in the market.Â 